2016
DOI: 10.1038/srep22839
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of spinal microglia repopulation following an acute depletion

Abstract: Our understanding on the function of microglia has been revolutionized in the recent 20 years. However, the process of maintaining microglia homeostasis has not been fully understood. In this study, we dissected the features of spinal microglia repopulation following an acute partial depletion. By injecting intrathecally Mac-1-saporin, a microglia selective immunotoxin, we ablated 50% microglia in the spinal cord of naive mice. Spinal microglia repopulated rapidly and local homeostasis was re-established withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 43 publications
(55 reference statements)
1
41
0
2
Order By: Relevance
“…However, it is noteworthy that even in naive animals, GFP+ cells were found in the spinal cord, which suggested that the leukocyte infiltration was independent of SNI induction (Fig. B), most likely caused by the irradiation as an experimental artifact …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, it is noteworthy that even in naive animals, GFP+ cells were found in the spinal cord, which suggested that the leukocyte infiltration was independent of SNI induction (Fig. B), most likely caused by the irradiation as an experimental artifact …”
Section: Resultsmentioning
confidence: 97%
“…In agreement, we found that when we applied a lethal irradiation, there is a significant engraftment of circulating cells (GFP + ) into the spinal cord of animals, even prior to SNI induction. Furthermore, besides BBB disruption there is evidence indicating that irradiation induces CNS resident cell death, especially microglia, which could cause leukocyte migration into the spinal cord in response to several inflammatory mediators released in the tissue . In this context, the increase in the number of GFP + cells in the spinal cord after SNI is simple explained by the fact that GFP + cells that engrafted after irradiation cells start to proliferate .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, there was controversial evidence of infiltration of macrophages and T cells into the spinal cord and dorsal root ganglia after CCI or transection of the rat sciatic nerve . Extravasation of leukocytes (macrophages and/or T cells) occurs in the lumbar spinal cord 3–14 days after peripheral L5 nerve transection.…”
Section: Discussionmentioning
confidence: 99%
“…One of the consequences of peripheral nerve injury is the entry of T cells from the circulation into the spinal dorsal horn parenchyma as part of the microglial reaction . Whether blood monocytes infiltrate the spinal cord in neuropathy remains controversial …”
Section: Introductionmentioning
confidence: 99%